1975
DOI: 10.1007/bf00158454
|View full text |Cite
|
Sign up to set email alerts
|

Observations of helium and hydrogen emission in quiescent prominences

Abstract: Observations of a number of helium triplet (~.210830, 4713, 4471, 3889, 4026) and hydrogea (H),, g, r/, 0) emission line intensities in six quiescent prominences are presented. The regions of prominence and neighboring corona were raster-scanned by the telescope, and all lines were measured concurrently at each point. The instrumental field of view was 5" • 20". The results are compared with previous observations and theory. In particular, the intensity of the 210830 emission relative to the other triplets is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 7 publications
1
49
0
Order By: Relevance
“…3 and 5 have net circular polarization (NCP), i.e., the wavelength integral of the Stokes V profile differs from zero. NCP can only be produced by variations of the magnetic field and velocity along the line-of-sight, which is well known from the early works to explain the broad-band circular polarization in sunspots by Illing et al (1975) and Auer & Heasley (1978) (see, e.g., Sánchez Almeida & Lites 1992, and references therein). This implies that strongly asymmetric Stokes V profiles showing NCP will always be present in sunspots, regardless of the spatial resolution of the observation across the line-of-sight.…”
Section: Discusionmentioning
confidence: 93%
“…3 and 5 have net circular polarization (NCP), i.e., the wavelength integral of the Stokes V profile differs from zero. NCP can only be produced by variations of the magnetic field and velocity along the line-of-sight, which is well known from the early works to explain the broad-band circular polarization in sunspots by Illing et al (1975) and Auer & Heasley (1978) (see, e.g., Sánchez Almeida & Lites 1992, and references therein). This implies that strongly asymmetric Stokes V profiles showing NCP will always be present in sunspots, regardless of the spatial resolution of the observation across the line-of-sight.…”
Section: Discusionmentioning
confidence: 93%
“…Lines of sight through the peripheral parts of a flux concentration that expands with height cross its boundary and, in the presence of strong external flows, thus sample significant magnetic field and velocity gradients. As a result, the Stokes-V profiles become asymmetric (Illing et al 1975) with a stronger blue lobe in the case of dominating external downflows (Grossmann-Doerth et al 1988b). The asymmetry arises from the fact that the wavelength shifts due to the Doppler effect and the Zeeman splitting have the same sign for one lobe, but opposite sign for the other lobe.…”
Section: General Propertiesmentioning
confidence: 99%
“…As a result, the Zeeman splitting is smaller and the V-profiles, particularly for the visible line, become strongly asymmetric. Illing et al (1975) have shown that asymmetric Stokes-V profiles arise in the presence of magnetic field and velocity gradients along the line of sight, the sign of the asymmetry being determined by the sign of the product of both gradients. On this basis, a mechanism leading to strongly asymmetric (and unshifted) Stokes-V profiles in the periphery of a static magnetic flux concentration has been suggested by Grossmann-Doerth et al (1988c) and Solanki (1989).…”
Section: Cut Through a Magnetic Featurementioning
confidence: 99%
“…Of special relevance is the asymmetry of the circular polarization profile, which is known to be related to the correlation between velocity and magnetic field gradients along the line-ofsight (LOS; Illing et al 1975). This effect has been exploited to build atmospheric models with such gradients to explain asymmetries around magnetic flux concentrations (Solanki & Pahlke 1988;Grossmann-Doerth et al 1988;Sánchez Almeida et al 1989;Solanki & Montavon 1993).…”
Section: Introductionmentioning
confidence: 99%